Applications of Electromagnetic Induction and Electrical Resistivity Tomography for Digital Monitoring and Assessment of the Soil: A Case Study of Al-Ahsa Oasis, Saudi Arabia - Maged Mohammed; Ahmed El Mahmoudi; Yousef Almolhem (Applied Sciences, 2022)
Al-Ahsa Oasis is one of the main and oldest agricultural centers in Saudi Arabia and one of the largest natural oases in the world. It is the largest irrigated agricultural oasis worldwide. The cultivated area is about 12,000 hectares in the region of Al-Ahsa. Groundwater was considered the main water source, if not the only source, for the different purposes of Al-Ahsa Oasis. However, due to groundwater depletion from these aquifers, treated wastewater is currently used to meet the shortage of irrigation water at Al-Ahsa Oasis. Today, several problems affect the agricultural productivity at Al-Ahsa Oasis, and modern geophysical techniques could contribute effectively to solving these problems; such problems are increasing soil salinity and the existence of a hardpan layer in some parts of the Al-Ahsa oasis. The soil texture is considered a critical factor to be taken into consideration. Therefore, the objectives of this study were to evaluate the effectiveness of modern geophysical techniques to study the agricultural aspects of Al-Ahsa oasis. Ten profiles of 2-D electrical tomography using SuperSting R8/IP 8 channel multielectrode resistivity and IP imaging system with 112 electrodes at one-meter spacing were implemented. Moreover, twenty electrical conductivity profiles were measured of 2240 points using EM38-MK2 at vertical mode with transmitter–receiver coils of 0.5 and one meter spacing. The results indicated that the salinity variation along the measured profiles was changed vertically and laterally due to the changes in the soil type, texture, moisture content, sabkha, and the whole oasis. Analysis and interpretation of the interpreted resistively tomograms of the ten 2-D profiles indicate remarkably the different geoelectric units of different hydrogeological conditions and soil texture across the oasis. These results will be of good utility for farmers, development sectors, and research institutions, especially in agriculture development studies, at Al-Ahsa Oasis, to ensure the sustainability of agriculture in this important historical Oasis.